IDENTIFICATION OF DRUG-RELATED PROBLEMS IN PATIENTS WITH UPPER ACUTE RESPIRATORY TRACT INFECTIONS IN TEBET SUBDISTRICT HEALTH CENTER - PUSPITASARI, ATIKA WAHYU; SERUNI, OLYVA CESSARI LARAS; NADHILAH, LINA (International Journal of Applied Pharmaceutics, 2020)
Objective: Acute respiratory tract infection (ARTI) is common and has the highest death rate in children, especially in growing countries such as Indonesia. The aim of the research is to identify drug-related problems (DRPs) in pediatric ARTI patients based on the DRP classification by Cipolle, Strand, and Morley, which included categories such as unnecessary drug therapy, need additional therapy, ineffective drug, dosage adjustments such as too low or too high, and adverse drug reaction which is drug interaction. Methods: The design of the study was cross-sectional and descriptive with a retrospective method. The sample of the study was the overall prescriptions to upper respiratory tract infection patients in Tebet Subdistrict Health Center from July to December 2018 that fulfilled all of the inclusion criteria, using the total sampling method. Total samples that were analyzed were from 179 sheets of prescription with a total of 498 prescriptions. Results: The results of the research based on each parameter were inaccurate drug selection (9.5%), inaccurate indication (12.8%), mismatched dose (79.9%), and drug interaction (0.6%). Conclusion: DRPs in ARTI pediatric patients resulted in a high-risk condition so that the health facilities need to improve their prescribing pattern and monitor and manage each therapy as well as do a routine prescription assessment to minimize the incidence of DRPs and achieve a rational drug usage.